A STUDY OF SCHOOL DROPOUTS - Hakim, Abdul (Jurnal Pendidikan, 2020)
Development in education sector is a very important thing to improve the quality of human resources. Therefore, the government established a 12-year compulsory education program in order to create quality human resources. However, school participation at the secondary school level needs to be increased so that the dropout rate can be controlled. This study uses secondary data from the March 2019 National Socio-Economic Survey (Susenas) which aims to identify variables that affect droupout rate for ages 7 to 18 years in Aceh. In addition, the purpose of this study is to determine the probability of school dropouts with certain characteristics. The analysis used is logistic regression, which is a method that explains the relationship between dichotomous response variable and a set of categorical explanatory variables. The result shows that the six variables selected were able to explain the variation of dropouts with a significance level of 5 percent. These variables are the education of household head, KIP/PIP ownership, household size, working children, poverty, and urban rural classification. The most dominant independent variable is ownership of KIP/PIP.